CLINIC, DIAGNOSTICS AND INDICATIONS FOR HOSPITALIZATION FOR PNEUMONIA IN CHILDREN - Ibatova Sh.M; Mamatkulova F.Kh., Ibragimova M., Akhmedov D. (EPRA International Journal of Research and Development (IJRD), 2022)
Pneumonia is an acute infectious disease, different in etiology, characterized by focal lesions of the lungs, which is more often manifested by intoxication, respiratory disorders, local physical changes in the lungs and the presence of an infiltrative shadow on a chest x-ray. The incidence of pneumonia is 15-20 per 1000 children in the first year of life. In outpatient settings, early diagnosis and rational therapy of pneumonia in children are serious problems. Pneumonia in children is still one of the urgent problems of pediatrics. [3,5,16,19,21]. Currently, there is an increase in the incidence of pneumonia in children and high mortality.